Storm child - Robotham, Michael, 1960- (New York : Scribner, 2024)
"The mystery of Evie Cormac's background has followed her into adulthood. As a child, she was discovered hiding in a secret room where a man had been tortured to death. Many of her captors and abusers escaped justice, unseen but not forgotten. Now, on a hot summer's day, the past drags Evie back as she watches the bodies of seventeen migrants wash up on a Lincolnshire beach. There is only one survivor, a teenage boy, who tells police their small boat was deliberately rammed and sunk. Psychologist Cyrus Haven is recruited by the police to investigate the murders--but recognizes immediately that Evie has some link to the tragedy. By solving this crime, he could finally unlock the secrets of her past. But what dark forces will he set loose? And who will pay the price?"--
Keywords: Forensic psychologists -- Fiction; Murder -- Fiction; Murder -- Investigation -- Fiction; Immigrants -- Fiction; Shipwrecks -- Fiction; Psychological fiction; Suspense fiction; Psychological fiction; Thrillers (Fiction); Novels